Telemedical management in patients waiting for transcatheter aortic valve implantation: the ResKriVer-TAVI study design - Mattig, Isabel; Koehler, Kerstin; Barzen, Gina; Hiddemann, Meike; Kugel, Elias; Roemmelt, Constantin; Mauckisch, Verena; Vockeroth, Clarissa; Stangl, Karl; Hoppe, Thomas; Koehler, Friedrich; Dreger, Henryk (Frontiers in Cardiovascular Medicine, 2024)
Aims: The majority of patients with severe aortic stenosis (AS) planned for transcatheter aortic valve implantation (TAVI) are elective outpatients. During the COVID-19 pandemic, the time between heart team decision and TAVI increased due to limited health care resources. We therefore implemented telemedical approaches to identify AS patients at risk for clinical deterioration during the wait time. The purpose of the prospective, randomized, controlled ResKriVer-TAVI study (DRKS00027842) is to investigate whether a digital concept of telemedical interventional management (TIM) in AS patients waiting for TAVI improves the clinical outcomes. Here, we report the study protocol of the ResKriVer-TAVI trial. Methods: ResKriVer-TAVI will enroll AS patients planned for elective TAVI. Randomization to the TIM group or standard care will be made on the day of the heart team decision. TIM will include a daily assessment of weight, blood pressure, 2-channel electrocardiogram, peripheral capillary oxygen saturation, and a self-rated health status until admission for TAVI. TIM will allow an optimization of medical therapy or an earlier admission for TAVI, if needed. Standard care will not include any additional support for AS patients. All patients of the TIM group will receive a rule-based TIM including standard operating procedures when a patient is crossing prespecified values of a vital sign. Results: The primary endpoint consists of days lost due to cardiovascular hospitalization and death of any cause within 180 days after the heart team decision. Major secondary endpoints include all-cause mortality within 365 days, number of telemedical interventions and adherence to TIM. Follow-up visits will be conducted at admission for TAVI as well as six and twelve months after heart team decision. Conclusions: ResKriVer-TAVI will be the first randomized, controlled trial investigating a telemedical approach before TAVI in AS patients. We hypothesize that primary and secondary endpoints of AS patients with TIM will be superior to standard care. The study will serve to establish TIM in the clinical routine and to increase the resilience of TAVI centres in situations with limited healthcare resources.